Vietnam - Ray, Nick (Lonely planet, 2005)
Contents: highlights; getting started; itineraries; the authors; snapshot; history; the culture; Tet festival; environment; food and drink; Hanoi; Northeast Vietnam; Northwest Vietnam; North-central Vietnam; central Vietnam; south-central coast,...